Records of bees (Hymenoptera: Apoidea) new to both Georgia and Transcaucasia revealed by DNA barcoding. Issue 2 (3rd April 2017) - Kirkitadze, Giorgi; Husemann, Martin; Paxton, Robert J.; Radzevičiūtė, Rita; Japoshvili, George
Abstract : Community composition of local pollinator assemblages, population dynamics and distribution patterns of many species are still poorly known, especially in little studied regions like Transcaucasia. We generated a total of 189 DNA barcodes from bees collected in 14 apple orchards in central and eastern Georgia to extend our knowledge of their distribution. Sequences (ca. 700 bp of the mitochondrial cytochrome oxidase I gene) were compared to the NCBI nucleotide database. Using a threshold of 98% similarity, analyses suggested that the sampled bees belong to 36 species of Apidae, Andrenidae, Halictidae, and Megachilidae. We report five bee species for the first time for Georgia: Andrena alfkenella Perkins, 1914, Halictus cochlearitarsis Dours, 1871, Nomada goodeniana (Kirby, 1802), Nomada ruficornis (Linnaeus, 1758) and Eucera nigrescens Pérez, 1879, four of which are also new for the Transcaucasia region. With these additions, the number of bee species known to occur in Georgia increases to 371.